HADIS QATL AL-MURTAD WA MAWAQIF AL-ULAMA' MINHU - Jannah, Shofiatul (RIWAYAH, 2022)
The Hadith of Killing Apostates and The Attitude of Scholars Toward it. This study discusses the hadith "Whoever leaves religion, kill him". The punishment for apostates mentioned in this hadith is the main basis among scholars in taking legal istinbath for apostates. Literally, this hadith commands the killing of apostates. This means that if a person who is Muslim leaves his religion, the punishment for him in this world is to be killed. Therefore, the issue of leaving religion is a problem that causes controversy among Islamic scholars. Some of them see that hadith is contrary to the meaning of the al-Qur'an, the Sunnah of the Prophet, and is contrary to freedom of religion. Therefore, the issue of apostasy is considered as one of the topics that raises complex problems and requires deep thought. This study aims to determine the attitude of scholars towards this hadith This study uses a descriptive analytical method by collecting information related to this hadith as well as collecting data about scholars’ attitudes on this hadith, then uses appropriate analysis tools. The results of this study are: The classical scholars agreed that anyone who apostatized from Islam without coercion should be killed, but they differed in opinion about repentance and its duration. They have different opinions about apostate women. However, contemporary scholars present several opinions, trying to provide a new understanding of this hadith. This hadith cannot be a general rule that applies to all situations and conditions.[Hadis Membunuh Orang Murtad dan Sikap Ulama terhadapnya. Kajian ini membahas hadis “Barang siapa keluar dari agama maka bunuhlah dia”. Hukuman bagi orang murtad yang disebutkan dalam hadis ini menjadi dasar utama dikalangan ulama dalam mengambil istimbath hukum bagi orang murtad. Secara harfiah, hadis ini memerintahkan membunuh orang murtad. Artinya jika seseorang yang beragama Islam meninggalkan agamanya maka hukuman kepadanya di dunia adalah bunuh. Oleh Karena itu, masalah keluar dari agama merupakan sebuah masalah yang meninmbulkan kontroversi di kalangan ulama Islam. Beberapa diantara mereka melihat bahwa hadis ini bertentangan dengan makna dhahir al-Qur’an, Sunnah Nabi, dan bertentangan dengan kebebasan beragama. Oleh karena itu, isu kemurtadan dianggap sebagai salah satu topik yang menimbulkan masalah yang komplek dan membutuhkan pemikiran yang mendalam. Penelitian ini bertujuan untuk mengetahuisikap ulama terhadap hadis ini. Penelitian ini menggunakan metode deskriptif analitis dengan mengumpulkan informasi-informasi yang berkaitan dengan hadis ini dan mengumpulkan data tentang sikap ulama terhadap hadis ini, kemudian menggunakan alat analisis yang sesuai. Adapun hasil penelitian ini yaitu para ulama klasik sepakat bahwa siapa pun yang murtad dari Islam tanpa paksaan harus dibunuh, tetapi mereka berbeda pendapat tentang taubat dan durasinya.Dan mereka juga berbeda pendapat tentang wanita yang murtad. Akan tetapi, ulama kontemporer menyampaikan beberapa pendapat, dan mencoba memberikan pemahaman baru tentang hadis ini. Bahwa hadis ini tidak bisa menjadi patokan umum yang berlaku untuk semua situasi dan kondisi.]